Influence of Bisphenol A on Type 2 Diabetes Mellitus - Provvisiero, Donatella Paola (Int J Environ Res Public Health, 2016)
Bisphenol A (BPA) is an organic synthetic compound employed to produce plastics and epoxy resins. It is used as a structural component in polycarbonate beverage bottles and as coating for metal surface in food containers and packaging. The adverse effects of BPA on human health are widely disputed. BPA has been recently associated with a wide variety of medical disorders and, in particular, it was identified as potential endocrine-disrupting compound with diabetogenic action. Most of the clinical observational studies in humans reveal a positive link between BPA exposure, evaluated by the measurement of urinary BPA levels, and the risk of developing type 2 diabetes mellitus. Clinical studies on humans and preclinical studies on in vivo, ex vivo, and in vitro models indicate that BPA, mostly at low doses, may have a role in increasing type 2 diabetes mellitus developmental risk, directly acting on pancreatic cells, in which BPA induces the impairment of insulin and glucagon secretion, triggers inhibition of cell growth and apoptosis, and acts on muscle, hepatic, and adipose cell function, triggering an insulin-resistant state. The current review summarizes the available evidences regarding the association between BPA and type 2 diabetes mellitus, focusing on both clinical and preclinical studies.